Some aspects of biodiversity conservation of fruit and berry cultures in the Central Kazakhstan (Experimental biology, 2016)
Result of many years researches have shown that main factors restricting an introduction of apple and pear cultivars are severe and prolonged frosts in the middle of a winter with little snow in the arid zone of Central Kazakhstan. Norcue, Norland and Norda apples from Canada, Uralskoe nalivnoe, Letnee polosatoe apples from Ural, Baganenok and Alenkii Tsvetochek apples from Siberia, and Barnaulskaya Krupnaya, Malinovka, Krasnoyarskaya Krupnaya and Veselinka pears from Siberia, Krasulya pear from Ural, Chizhovskaya, Petrovskaya and Lada pears from European part of Russia are very winter hardy to restricting factors of the arid zone of Central Kazakhstan. Altaiskaya Pozdnyaya, Bariyton, Lama, Galinka, Natasha and Rita Altaic black currants did not have injuries after the coldest winter of 2011/2012 during research period and had good yield. Result of many years researches have shown that strawberries are in need of covering in connection with little snow and severe winters. Preliminary researches of new strawberry cultivars have shown that Princess Diana strawberry (England) and Capri strawberry (Italy) are high-yielding cultivars. Kupchikha strawberry from Russia has good taste and high steadiness.
Keywords: untroduction; limit factor; cultivar; apple-tree; pear-tree; black currant; strawberry